Canine meningiomas treated with three‐dimensional conformal radiation therapy require magnetic resonance imaging to avoid a geographic miss. Issue 6 (28th June 2018) - Berlato, Davide; Zwingenberger, Allison L; Ruiz‐Drebing, Matias; Pradel, Julie; Clark, Nicola; Kent, Michael S
Abstract: Exact target volume definition is an essential prerequisite for modern radiotherapy treatment planning. Contouring the gross tumor volume of brain tumors on computed tomography (CT) images coregistered with magnetic resonance images is standard practice in human medicine. In this retrospective study, including only cases with an imaging diagnosis of meningioma, we hypothesized that the gross tumor volume contoured from the contrast‐enhanced magnetic resonance imaging (MRI) (gross tumor volume‐MRI) is larger when compared to the gross tumor volume contoured using contrast‐enhanced CT (gross tumor volume‐CT). A total of 22 dogs were included in the study. Interestingly, there was a significant statistical difference between the gross tumor volume‐CT and the gross tumor volume‐MRI ( P = 0.001). The gross tumor volume‐MRI was larger than the gross tumor volume‐CT in all, but two cases. The mean ratio between gross tumor volume‐MRI and gross tumor volume‐CT was 1.43 (range 0.84–4.00). The mean overlap between gross tumor volume‐CT and gross tumor volume‐MRI was 68% (range 22–86%), while a mean of 26% of the composite gross tumor volume was defined only by MRI (range 4–76%) and a mean of 6% only by CT (range 0–22%). These findings suggest that CT and MRI are complementary modalities in radiation planning of meningiomas and their composite volume should be used to avoid geographical miss of neoplastic tissue. When the MRI is not available for planning, a margin of 0.3 cm around the gross tumor volume‐CT could reduce the probability of a geographical miss. However, such numerical correction cannot be applied to the clinical practice until it is validated in a properly designed treatment planning study.